Respostas
respondido por:
2
a) x²-5x+6
x= -b+/-√b²-4ac / 2a
x= 5+/- √25-24 / 2
x= 5 +/-√ 1 / 2
x= 5+/-1 / 2
x= 5+1 / 2
x= 6 / 2
x= 3
x'= 5-1 / 2
x'= 4 / 2
x'= 2
b) x²+5x-6=0
x= -5 +/-√25+24 / 2
x= -5 +/- √49 / 2
x= -5 +/- 7 / 2
x= -5+7 / 2
x= 2 / 2
x= 1
x'= -5-7 / 2
x'= -12 / 2
x'= -6
x= -b+/-√b²-4ac / 2a
x= 5+/- √25-24 / 2
x= 5 +/-√ 1 / 2
x= 5+/-1 / 2
x= 5+1 / 2
x= 6 / 2
x= 3
x'= 5-1 / 2
x'= 4 / 2
x'= 2
b) x²+5x-6=0
x= -5 +/-√25+24 / 2
x= -5 +/- √49 / 2
x= -5 +/- 7 / 2
x= -5+7 / 2
x= 2 / 2
x= 1
x'= -5-7 / 2
x'= -12 / 2
x'= -6
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás